The irrigation influence on agricultural intensification in Serbia - Potkonjak, Svetlana; Zoranović, Tihomir; Mačkić, Ksenija (Economics of Agriculture, 2010)
The factors that influence on the intensification of agriculture on our estates (internal and external) are analyzed. Depending on the level of development and measures of agricultural policy, intensification process can be encouraged on many ways. In our case, the influence of constructing regional hydro system to increase the intensity (of production and economic effects) was investigated. Depending on the size of the hydro system, the volume of invested funds, as well as suggestions about possible restruction of the production, doubling of the economic and production effects can be achieved, on the condition that production management is in function of achieving our objectives. Realistically, in this case, the regional hydro system should be holders of intensification. They initiate the development of manufacturing industry and provide more quality goods for processing and market. Besides positive effects (direct and indirect) impact of irrigation on intensification, during long-term use on the same land, some negative effects were noticed (soil salinization, deterioration of water quality, irrigation erosion).